PENGARUH MINAT BACA, MOTIVASI BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI TAHUN ANGKATAN 2014-2016 - -, Dhenise Kusuma -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This study aims to examine the presence or absence of (1) whether there is effect variables of reading interest, learning motivation and the environment of peers in silmutaneously toward the achievement of students of economic education class of 2014-2016, (2) whether there is effect of reading interest variable partially to the learning achievement student of economic education class of 2014-2016, (3) whether there is effect of learning motivation variable partially to the  learning achievement student of economic education class of 2014-2016, (4) whether there is effect of influence of peer environmental variables partially to the learning achievement student of economic education class of 2014 -2016. The type of this research is descriptive quantitative with survey method. The population in this research were all student of economic education class of 2014-2016, amounting to 180 students with sample of 124 respondents. Techniques sampling used in this research were Proportionate Stratified Random Sampling by lottery. Data collection is done by questionnaire technique and documentation technique. The validity of the data obtained through tryout conducted to 30 respondents. The data analysis technique used is the technique of  multiple linear regression analysis. Based on the result of this research, it can be concluded that: (1) Based on the results of F test obtained Fcount > Ftable (67,665 > 2,68) with a probability value of < 0,05 is equal to 0.000, so that H0 rejected and Ha accepted. It means that there is significant effect of reading interest variables, learning motivation variables and the environment of peers variables silmutaneously towards student learning achievement, (2) Based on the results of t test interest reading variable obtained value tcount > ttable (3,648 > 1,979) with a probability value of < 0,05 is equal to 0.000 so that H0 rejected and Ha accepted. It means that there is significant effect of  reading interest variables partially toward student learning achievement, (3) Based on the results of t test learning motivation variable obtained value tcount > ttable (3,710 > 1,979) with a probability value of < 0,05 is equal to 0.000 so H0 rejected and Ha accepted. It means that there is a significant effect of  learning motivation variables partially toward student learning achievement, (4) Based on the results of t test peer environmental variables obtained value tcount > ttable (6,580 > 1,979) with probability value of < 0,05 is equal to 0.000, so H0 is rejected and Ha accepted. It means that there is a significant effect of peer environmental variables partially toward student learning achievement.